Using modified guided writing and role-play to motivate students to practice speaking - Susan Dewi; Yohanes Gatot Sutapa Yuliana; Melti Oktavianda (UPT Bahasa Universitas Tanjungpura, 2020)
The ability to speak in English is one of the requisite skills for vocational high school students majoring in hospitality training. However, most tenth-grade students manifested insufficient skills in speaking English, which resulted in low confidence in speaking. To cope with the challenge, the researchers implemented modified role-play and guided writing to stimulate students in speaking English in classroom action research. The procedure of the research consisted of planning, acting, observing and reflecting. The researchers employed observation, questionnaire, documentation and field notes in collecting the data. The research findings presented that the students’ motivation to practice their speaking had increased significantly. Thus, the researchers conclude that role-play and guided writing can be used as a communicative activity where students can simultaneously practise and improve their proficiency in communicating. The researchers also propose suggestion to fellow English teachers to effectively manage the time as well as engaging media to create an enjoyable atmosphere in the teaching-learning process through role-play and guided writing.